Peran Pendidikan Islam dalam Mempertahankan Integrasi Sosial: Pandangan Emile Durkheim dalam Sosiologi Pendidikan - Nur Indri Yani Harahap; Silfia Hanani; Muhamad Iqbal; Andy Riski Pratama (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research examines the role of Islamic education in maintaining social integration through the lens of Emile Durkheim's sociology of education. Emile Durkheim, a major figure in sociology, has developed a theory about the importance of educational institutions in maintaining social solidarity and preventing disintegration in society. The research method used is literature study, by collecting and analyzing various relevant library sources. The results of this research underline that Islamic education has great potential in maintaining social integration in Muslim societies. Islamic educational institutions can act as the main agents in forming moral values, strengthening social solidarity, and building a strong social identity. This research provides an in-depth understanding of how the principles of Emile Durkheim's sociology of education can be applied to the context of Islamic education, and the results can provide guidance for the development of educational policies that support sustainable social integration in Muslim societies.